Some Reflections on HOTS dimension of Education in Prophet's Era - Rahmawati, Fitra Awalia; Zain, Muhammad Abdurrozaq Purnama; Salam, Muhammad Fikri; Umar, Muhammad Yudistira Iqbal (Proceeding International Conference on Science and Engineering, 2021)
Abstract. The development of Islamic teachings in Prophet Muhammad SAW and his companions was the development of the peak of its heyday, it can be seen how the purity of Islam itself, with the main actors and factors, namely Prophet Muhammad SAW. When viewed from various scientific aspects, it is clear that the guidance of the Prophet Muhammad towards Muslims at that time reflected a Higher Order Thinking Skill; with its aspects are critical thinking, creativity, communication, and collaboration. Through the encouragement of revelation to "think" and carry out scientific activities as well as generate good charity for others. This literature research takes data in the form of literature on the history and models of education in the era of the Prophet based on the Sirah Nabawiyah literature. This study found that the HOTS aspect of the Prophet's guidance was reflected in the liberation of humans from myths (encouraging critical thinking), amar ma'ruf nahi munkar and helping others, to honesty in various matters. All of them systemically result in Muslims being motivated to do good deeds in various creative forms. From the events of the hijrah to his victory in various wars to fight for Islam.